Large-scale biofilm cultivation of Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 for physiologic studies and drug discovery - PARRILLI, ERMENEGILDA; RICCIARDELLI, ANNARITA; CASILLO, ANGELA; Sannino, Filomena; Papa, Rosanna; Tilotta, Marco; Artini, Marco; Selan, Laura; CORSARO, MARIA MICHELA; TUTINO, MARIA LUISA (Extremophiles, 2016)
Microbial biofilms are mainly studied due to detrimental effects on human health but they are also well established in industrial biotechnology for the production of chemicals. Moreover, biofilm can be considered as a source of novel drugs since the conditions prevailing within biofilm can allow the production of specific metabolites. Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 when grown in biofilm condition produces an anti-biofilm molecule able to inhibit the biofilm of the opportunistic pathogen Staphylococcus epidermidis. In this paper we set up a P. haloplanktis TAC125 biofilm cultivation methodology in automatic bioreactor. The biofilm cultivation was designated to obtain two goals: (1) the scale up of cell-free supernatant production in an amount necessary for the anti-biofilm molecule/s purification; (2) the recovery of P. haloplanktis TAC125 cells grown in biofilm for physiological studies. We set up a fluidized-bed reactor fermentation in which floating polystyrene supports were homogeneously mixed, exposing an optimal air–liquid interface to let bacterium biofilm formation. The proposed methodology allowed a large-scale production of anti-biofilm molecule and paved the way to study differences between P. haloplanktis TAC125 cells grown in biofilm and in planktonic conditions. In particular, the modifications occurring in the lipopolysaccharide of cells grown in biofilm were investigated.